Manipulating regulatory T cells: is it the key to unlocking effective immunotherapy for pancreatic ductal adenocarcinoma? - Smith, Henry; Arbe-Barnes, Edward; Shah, Enas Abu; Sivakumar, Shivan (Frontiers in Immunology, 2024)
The five-year survival rates for pancreatic ductal adenocarcinoma (PDAC) have scarcely improved over the last half-century. It is inherently resistant to FDA-approved immunotherapies, which have transformed the outlook for patients with other advanced solid tumours. Accumulating evidence relates this resistance to its hallmark immunosuppressive milieu, which instils progressive dysfunction among tumour-infiltrating effector T cells. This milieu is established at the inception of neoplasia by immunosuppressive cellular populations, including regulatory T cells (Tregs), which accumulate in parallel with the progression to malignant PDAC. Thus, the therapeutic manipulation of Tregs has captured significant scientific and commercial attention, bolstered by the discovery that an abundance of tumour-infiltrating Tregs correlates with a poor prognosis in PDAC patients.Herein, we propose a mechanism for the resistance of PDAC to anti-PD-1 and CTLA-4 immunotherapies and re-assess the rationale for pursuing Treg-targeted therapies in light of recent studies that profiled the immune landscape of patient-derived tumour samples. We evaluate strategies that are emerging to limit T reg -mediated immunosuppression for the treatment of PDAC, and signpost early-stage trials that provide preliminary evidence of clinical activity. In this context, we find a compelling argument for investment in the ongoing development of Treg-targeted immunotherapies for PDAC.